How serum magnesium level is related to severity of asphyxia - Khare, Atul Kumar; Singh, Kirti; Paliwal, Ashish; Sharma, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Perinatal asphyxia is a most common cause of neonatal death. Magnesium, the second most common intracellular cation, may play a role in neuroprotection. Methods: This observational study was undertaken in the Department of Gynecology and Pediatrics in GMC, Shahdol from January 2021 to June 2023. The term babies were included with congenital anomaly, diabetic mother, IUGR, and mother receiving magnesium therapy during labour were excluded. Data analysis was conducted using IBM SPSS statistical software (version 22.0). Results: Out of 46 newborns, mild to moderated asphyxia and severe asphyxia were presenting 32 (69.6%) and 14 (30.4%) cases respectively. HIE-I were 20 (43.5%), HIE II-16 (34.8%) and HIE III-10 (21.7%). The mean serum magnesium level in neonates with mild to moderate asphyxia was 2.1±0.3 and with severe asphyxia 1.5±0.5 respectively (p=0.001). Serum magnesium was significantly low in severe birth asphyxia as compared to mild to moderate (p=0.001) and level was significantly low in HIE stage 3. The difference in serum magnesium between HIE 1 and 3 and HIE 2 and HIE 3 was statistically significant (p=0.003 and p=0.009, respectively). A significant correlation between serum magnesium and Apgar score at 1 minute (Pearson’s correlation coefficient, r=0.518, p=0.001) and score at 5 minutes was also statistically significant (Pearson’s correlation coefficient, r=0.379, p=0.009). Conclusions: Neonates with severe asphyxia and HIE- grade III have significant hypomagnesemia. Asphyxia can lead to hypomagnesemia, and it is recommended to evaluate levels of magnesium in neonates with asphyxia as a routine test.